2015
DOI: 10.1039/c4ta06869f
|View full text |Cite
|
Sign up to set email alerts
|

High-rate, high-density FeSb–TiC–C nanocomposite anodes for lithium-ion batteries

Abstract: High-density, high-rate FeSb-TiC-C nanocomposite alloy anodes composed of varying amounts of FeSb, TiC, and conductive carbon black have been synthesized by heating the metallic precursors first followed by high-energy mechanical milling (HEMM) of the product with carbon black. The synthesis method allows for a systematic variation of the TiC and carbon contents within the electrode so that the effects of each component on the electrochemical performance can be understood. The FeSb-TiC-C samples display high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…Neither FeSn 2 eTiC nor SneTiC have carbon black as a final component in their composite structure and they exhibit much lower first cycle losses than FeSn 2 eC, which has carbon black. This is in agreement with previous studies attributing higher first cycle irreversibility to carbon black in composite electrodes [25]. In addition, the use of FeSn 2 intermetallic instead of Sn as the active material results in significant increase in capacity retention as demonstrated by the higher capacity values at 100 cycles for both FeSn 2 eTiC and FeSn 2 eC relative to SneTiC.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Neither FeSn 2 eTiC nor SneTiC have carbon black as a final component in their composite structure and they exhibit much lower first cycle losses than FeSn 2 eC, which has carbon black. This is in agreement with previous studies attributing higher first cycle irreversibility to carbon black in composite electrodes [25]. In addition, the use of FeSn 2 intermetallic instead of Sn as the active material results in significant increase in capacity retention as demonstrated by the higher capacity values at 100 cycles for both FeSn 2 eTiC and FeSn 2 eC relative to SneTiC.…”
Section: Resultssupporting
confidence: 90%
“…Similar capacity fade has been observed in previous studies of alloying anode materials where carbon black was the reinforcing phase [25]. The FeSn 2 eTiC material demonstrates both good early cycling as well as stable capacity for 100 cycles.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…9 Under air and reducing agents, lead ions form lead oxide and copper without further oxidation (eqn (2)). 9 Under air and reducing agents, lead ions form lead oxide and copper without further oxidation (eqn (2)).…”
Section: Methodsmentioning
confidence: 99%
“…Metal oxides usually exhibit low volume changes during cycling, and the rst lithiation forms metal clusters surrounded by lithium oxides and lithium metal alloys that act as buffer layers for accommodating the cyclic volume changes, thus possibly enhancing cycling performance. 9 However, depositing an even carbon coating on metal oxide surfaces is not possible at the molecular level. For example, Li et al reported the one-step hydrothermal synthesis of Nb 2 O 5 /carbon composites with enhanced electrochemical performance (specic capacity ¼ 100 mA h g À1 at a current density of 500 mA g À1 ).…”
Section: Introductionmentioning
confidence: 99%